Influence of Cement Dose on the Durability of Structures in Stabilized Compressed Earth Blocks - Banakinao, Sinko; Drovou, Soviwadan; Attipou, Kodjo (International Journal of Sustainable Construction Engineering and Technology, 2022)
Structures in stabilized Compressed Earth Blocks (CEB), and more precisely the exterior walls (exposed to rainwater) or interior walls (exposed to spray water room, e.g.: bathroom) constructed with sand clay of class 2, suffer from decrepitude and crumbling, which are degradations due to environmental stresses. In order to solve this problem of degradations, it is necessary to find a minimum dosage level of cement that ensures the resistance to rupture and environmental stresses, in particular the aggression from rainwater and/or rise in moisture by capillarity, penetration by gravity, by suction or internal condensation. Two tests of durability have been conducted to simulate the two phenomena. These are a cyclic test of alternated wetting and drying to simulate the phenomenon of rise in moisture and a spray test to simulate the aggression from rainwater. The results of these tests show that a minimum dosage of 10% is sufficient to strengthen durably the walls against environmental stresses.